Validation of UV-VIS Spectrophotometric Method For The Penetration Test of Pickering Emulsion Diclofenac Diethylamine - Hutami, Shabrina Nindya; Kuncahyo, Ilham; Aisiyah, Siti; Adi Nugroho, Septiawan; Roro Sri Wulandari, Raden (Journal of Herbal, Clinical and Pharmaceutical Science (HERCLIPS), 2025)
Pickering emulsions are emulsions stabilized by solid particles that adsorb at the interface of both phases, acting as emulsifiers without requiring amphiphilic surface properties (hydrophilic and hydrophobic segments) to stabilize the emulsion (Hutami et al., 2024). This approach allows the formulation to avoid the use of potentially toxic surfactants (Wu et al., 2020). The objective of this study was to validate an analytical method for the penetration test using a Franz diffusion cell for a diclofenac diethylamine Pickering emulsion formulation, ensuring that the UV-Vis spectrophotometric analysis method is reliable by fulfilling all validation requirements. Based on the validated parameters, the assay procedure for the penetration test (Franz diffusion cell) of the diclofenac diethylamine Pickering emulsion using UV-Vis spectrophotometry met the established criteria. The linearity with a correlation coefficient (r) of 0.9997, indicating excellent linearity. Precision testing showed a %RSD of 0.608%, indicating good repeatability. Accuracy testing at 80%, 100%, and 120% concentration levels yielded recovery results ranging from 99.822% to 101.157%. The Limit of Detection and Limit of Quantification, calculated from the absorbance at the lowest concentrations, were found to be 6.46×10⁻⁴ ppm and 1.96×10⁻³ ppm, respectively. Therefore, the method is considered valid, having met all analytical method validation parameters